Jazz, libertà ed emancipazione femminile (con un’intervista a Maria Pia De Vito) - Marino, Stefano (Scenari, 2021)
Jazz music has often, or always, been considered by historians, music critics and also musicians as a kind of music essentially connected to freedom and emancipation. From an inner or strictly musical point of view, this has always been associated to such fundamental features and distinctive qualities of this music as improvisation (which, of course, can be understood in turn in different ways) and interplay, the free dialogue or conversation between the musicians during the performance. From an outer or extra-musical point of view, this has always been associated to the roots of jazz music in the spirituals and the blues, and in the “black” heritage and spirit that they convey, thus including the struggle for emancipation from a condition slavery, racism, segregation, subjugation etc. In this article I first analyze some aspects of this connection between jazz, freedom and emancipation, and then ask if what is true for the struggle for black emancipation that this music has expressed throughout the decades (especially with jazz “styles” or “currents” like be-bop and free jazz) also holds true for the struggle for women’s emancipation that has characterized to no less extent the history of the 20th century. The article also includes an original interview on the topic with one of the most important and celebrated Italian jazz singers, Maria Pia De Vito, who contributes to shed light on the guiding question if, when and how much jazz has contributed to women’s freedom and emancipation.